Intrafamilial Genotyping of Helicobacter pylori from Faecal DNA - M. McMillan; W. G. MacKay; C. L. Williams; A. J. Shepherd; C. Malcolm; L. T. Weaver (Gastroenterology Research and Practice, 2011)
Helicobacter pylori infection, often acquired in early childhood, is a global cause of undernutrition, gastritis, peptic ulcer disease and gastric carcinoma. This study tested the feasibility of using H. pylori shed in the faeces as a source of DNA for non-invasive epidemiological studies. H. pylori DNA was chemically recovered and isolated using a specific biotinylated oligonucleotide probe with magnetic capture from 28 H. pylori positive faecal samples obtained from children attending hospital for the investigation of suspected H. pylori infection, together with close family members. Random amplification of polymorphic DNA (RAPD) was subsequently used to discriminate each isolate. 93% of stool samples selected were typeable. Parent, child and sibling samples were compared and similarities determined. Phylogenetic analysis showed that H. pylori DNA obtained from the faeces can be used to genotype individual strains, offering a means of studying intrafamilial transfer of this microorganism.